The Applicability Of Demirjians And Nollas Dental Age Estimation Methods For Children In Surabaya Indonesia - Arofi Kurniawan; An'nisaa Chusida; Maria Istiqomah Marini; Beta Novia Rizky; Beshlina Fitri Widayanti Roosyanto Prakoeswa; Patricia Shankar Jethani; Jeremy Matthew Emmanuella Lomo; Rafi Danabrata; Anand Marya; Aspalilah Alias; Rabiah Al-Adawiyah Rahma (International Association for Paleodontology, 2025)
Index by WOS/SCOPUS/ERA (Tier 2)